Genetic ablation of Lmp2 increases the susceptibility for impaired cardiac function - Trogisch, Felix A.; Koser, Franziska; Michel, Synje; Liem, David A.; Florea, Bogdan I.; Hecker, Markus; Drews, Oliver (Frontiers in Molecular Biosciences, 2024)
Proteasome degradation is an integral part of cellular growth and function. Proteasomal intervention may mitigate adverse myocardial remodeling, but is associated with the onset of heart failure. Previously, we have demonstrated that increasing abundance of cardiac Lmp2 and its incorporation into proteasome complexes is an endogenous mechanism for proteasome regulation during hypertrophic remodeling of the heart induced by chronic β-adrenoreceptor stimulation. Here, we investigated whether Lmp2 is required for myocardial remodeling not driven by inflammation and show that Lmp2 is a tipping element for growth and function in the heart but not for proteasome insufficiency. While it has no apparent impact under unchallenged conditions, myocardial remodeling without Lmp2 exacerbates hypertrophy and restricts cardiac function. Under chronic β-adrenoreceptor stimulation, as seen in the development of cardiovascular disease and the manifestation of heart failure, genetic ablation of Lmp2 in mice caused augmented concentric hypertrophy of the left ventricle. While the heart rate was similarly elevated as in wildtypes, myocardial contractility was not maintained without Lmp2, and apparently uncoupled of the β-adrenergic response. Normalized to the exacerbated myocardial mass, contractility was reduced by 41 % of the pretreatment level, but would appear preserved at absolute level. The lack of Lmp2 interfered with elevated 26S proteasome activities during early cardiac remodeling reported previously, but did not cause bulk proteasome insufficiency, suggesting the Lmp2 containing proteasome subpopulation is required for a selected group of proteins to be degraded. In the myocardial interstitium, augmented collagen deposition suggested matrix stiffening in the absence of Lmp2. Indeed, echocardiography of left ventricular peak relaxation velocity (circumferential strain rate) was reduced in this treatment group. Overall, targeting Lmp2 in a condition mimicking chronic β-adrenoreceptor stimulation exhibited the onset of heart failure. Anticancer therapy inhibiting proteasome activity, including Lmp2, is associated with adverse cardiac events, in particular heart failure. Sparing Lmp2 may be an avenue to reduce adverse cardiac events when chronic sympathetic nervous system activation cannot be excluded.